Formulation and Evaluation of Pregabalin Loaded Eudragit S100 Nanoparticles - Senthilnathan, B.; Maheswaran, A.; Gopalasatheeskumar, K.; Masilamani, K.; Raihana Z., Edros (Penerbit Universiti Malaysia Pahang, 2016)
In this work, polymeric nanoparticles containing Pregabalin was prepared and optimized the ideal concentration of polymer based on its in vitro release profile for a period of 24hrs.The nanoparticles were prepared by solvent displacement method using various concentrations of Eudragit S100 (EPNP1-EPNP5). The prepared nanoparticles were characterized for its particle size, zeta potential, drug content, entrapment efficiency and invitro drug release profile. The preformulation study results confirmed the compatibility between the drug and other excipients used in the formulation. The optimized formulation was selected based on its particle size, entrapment efficiency and in vitro drug release profile. The formulation which contains 300mg of Eudragit S100 (EPNP5) was selected as optimized concentration for the controlled release of Pregabalin for a period of 24hrs.